PERAN PEMERINTAH DESA DALAM PENURUNAN STUNTING DI DESA KESETNANA, KECAMATAN MOLLO SELATAN, KABUPATEN TIMOR TENGAH SELATAN - Taosu, Richel; Toda, Hendrik; Rene, Mariayani Oktafiana (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aims to analyze the role of the Kesetnana Village Government in reducing stunting through three main functions: as a motivator, facilitator, and mobilizer. This research employs a descriptive qualitative approach using a case study method. Data collection techniques included observation, in-depth interviews, and documentation. The findings indicate that the village government acts as a motivator by conducting continuous outreach and education about stunting and balanced nutrition. As a facilitator, the government provides physical facilities such as PKK buildings, village clinics, and anthropometric tools to support nutritional interventions. Meanwhile, its role as a mobilizer is reflected in cross-sector collaboration and the utilization of village funds and external aid for nutrition and sanitation programs. In conclusion, the Kesetnana Village Government has effectively carried out these roles to reduce stunting prevalence, despite facing challenges related to community participation and limited resources.